Faktor Penerapan Fintech Untuk Perkembangan dan Eksistensi Koperasi di Kabupaten Lombok Tengah - Ardiansyah, Lalu Yayan; Prasetyo, Rahman (Income : Digital Business Journal, 2023)
The development of cooperatives in central Lombok in the last five years has increased every year. Technological developments force financial institutions to always innovate to increase efficiency and effectiveness in the institution's operational activities. several cooperatives in Central Lombok district have not yet used fintech in their institution's operational activities. Based on the findings and several previous studies, an approach is needed regarding the nature of cooperatives that have not used financial technology to facilitate operational activities, facilitate transactions, and reach a wider range of customers in cooperatives in Central Lombok district. The selected qualitative approach is related to phenomena that occur in society so as to understand the subject matter. In this study, the research object was given a code to make it easier for researchers and readers to categorize research objects. The findings from this study include cooperative constraints in implementing fintech in the form of application development used and parties that can develop fintech applications that can be explored for collaboration by cooperatives. Lack of education about fintech to cooperative employees and cooperative partners. Therefore it is necessary to develop and train cooperative employees and partners.